2010
DOI: 10.1158/1538-7445.am10-lb-326
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-326: Synergistic therapeutic effects of cytokine-induced killer (CIK) cell and temozolomide against glioblastoma

Abstract: The presence of active immunity within the brain supports the possibility of effective immunotherapy for glioblastoma (GBM). To provide a clinically-relevant adoptive immunotherapy for GBM using ex vivo expanded cytokine-induced killer (CIK) cells, the treatment capability of CIK cells, either alone or in combination with temozolomide (TMZ) were evaluated. Human CIK (hCIK) cells were cultured from PBMC using activating anti-CD3 antibody and IL-2, which were 99% CD3+, 91% CD3+CD8+ and 29% CD3+CD56+. In vitro, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“… 27,51 However, combination treatment with TMZ and adoptively transferred human cytokin-induced killer cells showed synergistic therapeutic efficacy in a xenograft mouse model with transplanted U-87MG cells. 52 Such a synergistic therapeutic effect might be also envisaged with γδ T cells.…”
Section: Discussionmentioning
confidence: 99%
“… 27,51 However, combination treatment with TMZ and adoptively transferred human cytokin-induced killer cells showed synergistic therapeutic efficacy in a xenograft mouse model with transplanted U-87MG cells. 52 Such a synergistic therapeutic effect might be also envisaged with γδ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that immunotherapy with TMZ is feasible for glioma treatment (Kim et al, 2007;Jin et al, 2011). Recent preclinical studies have shown that vaccination with dendritic cells followed by chemotherapy increases glioma patient survival (Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive immunotherapy is dedicated to taking advantage of cytokine-induced killer cells (CIK cells) and lymphokine-activated killer cells (LAK cells) to treat GBM. For CIK cells, human PBMCs are traditionally required to be incubated for 4 weeks with numerous cytokines to generate CIK cells [ 43 ]. Moreover, LAK cells, as immunotherapeutic agents, also have some disadvantages, such as a short in vivo lifespan, poor cytotoxicity, and numerous side effects [ 44 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth was determined with an animal magnetic resonance imaging (MRI) system (PharmaScan 7T, Bruker, Germany) on days 7, 14, 21 and 28. When the first MRI scanning confirmed the tumor formation on the 7th day after the tumor cells implantation, the PD-1 inhibited and non-inhibihted IL-2-stimulated NK cells (5×10 6 , in 100μl PBS) and PBS (negative control) were intravenously injected into the mice containing GL261GSCs tumors once a week for four weeks [ 29 ]. The tumor volume was calculated by measuring the MRI of the largest tumor portion and applying the following formula: (width) 2 x length x 0.5.…”
Section: Methodsmentioning
confidence: 99%